ISLAM AND SOCIAL DEVELOPMENT: A REFORM VISION FROM SUDAN - Russina A Eltoum, (Journal of Islamic, Social, Economics and Development, 2023)
This paper reviews the role of religion in the development of society in light of the views of Al-Ustaz Mahmoud M Taha, who was executed by the Sudanese government in 1985. Taha’s views were considered modern and reformatory. However, they were also considered controversial and led to his conviction of apostasy and execution. This paper discusses some of the views presented in his book “Religion and Social Development” and examines their potential to provide suggestions for the development of individuals and societies. Religion from the perspectives of intellectuals, such as Al-Ustaz Mahmoud M Taha is of an essential role in the development of individuals and societies alike. These kinds of views place religion in an established position and prevent it from the deviations of thought that lead to extremism and terrorism.